The effect of Yb3+ on corrosion of lead oxychloride tellurite glasses - Mohd. Yassin, Muhammad Abdullah Izat (2013)
A series of tellurite glasses based on (80-x)TeO2-10PbO-10PbCl2-xYb2O3 where 0.0 = x = 3.0 mol% had successfully been prepared by conventional melt quenching technique. The glass was stable in air and the structural phase was determined using X-ray diffraction technique. The transition temperature, Tg and the crystallization temperature, Tc were determined using differential thermal analyser, DTA. Meanwhile, the density and molar volume of the glass were determined by using Archemedes technique. The glass durability was determined by the measurement of its corrosion rate in acidic solution, alkaline solution and in distilled water. It was found that the glass was amorphous as no peak existed in the X-ray diffraction spectra. It was also found that the Tg and Tc increased as the Yb3+ content was increased. It was observed that the glass density increased while molar volume decreased with increasing Yb3+ content. The corrosion rate in acidic solution, alkaline solution and distilled water were in the range of (2.46 to 52.04) ? 10-7 gmm-2 day-1, (0.90 to 2.87) ? 10-7 gmm-2day-1 and (1.13 to 2.59) ? 10-7 gmm-2day-1, respectively. It was generally expected that the degradation of glass was due to the ion exchange mechanism and diffusion controlled process